1997
DOI: 10.1021/jf960809o
|View full text |Cite
|
Sign up to set email alerts
|

Composition Factors Affecting the Water Vapor Permeability and Tensile Properties of Hydrophilic Zein Films

Abstract: Transparent unplasticized zein films were prepared in aqueous ethanol or acetone. Tensile properties indicated that films prepared in acetone were stronger but less flexible than those prepared in ethanol. Both types of films, however, were too brittle for most applications. Films containing a glycerol:poly(propylene glycol) ratio of 1:3 exhibited elongation values almost fifty times greater than glycerol-plasticized films. Incorporation of cross-linking agents into zein films resulted in approximately a 2−3-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
119
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 8 publications
21
119
3
Order By: Relevance
“…In general, it can be concluded that high ratio of plasticizer to corn-zein amount resulted in a rise in WVP of coated PP films while films with zein coating having low plasticizer content have high barrier to water vapor. Several authors studied the influence of the plasticizer content on barrier properties of zein films, and they showed that there is an increase in WVP of films with an increase in plasticizer content (Lai and Padua, 1997;Parris and Coffin, 1997;Ghanbarzadeh et al, 2006b;Rakotonirainy and Padua, 2001). The results of these studies agree with those reported in this study.…”
Section: Water Vapor Permeability Of Coated Filmssupporting
confidence: 89%
“…In general, it can be concluded that high ratio of plasticizer to corn-zein amount resulted in a rise in WVP of coated PP films while films with zein coating having low plasticizer content have high barrier to water vapor. Several authors studied the influence of the plasticizer content on barrier properties of zein films, and they showed that there is an increase in WVP of films with an increase in plasticizer content (Lai and Padua, 1997;Parris and Coffin, 1997;Ghanbarzadeh et al, 2006b;Rakotonirainy and Padua, 2001). The results of these studies agree with those reported in this study.…”
Section: Water Vapor Permeability Of Coated Filmssupporting
confidence: 89%
“…Although there are some reports on using DAS as cross-linking agent for various proteins, such as soy protein isolate [26,27], collagen [28], corn zein [29], flour starch-protein [30], and whey protein [31], to the best of our knowledge there are very few studies on keratin materials cross-linked with DAS. We previously reported that the mechanical properties, thermal stability, and water vapor barrier property of FK/PVA blended films could be improved by DAS-induced cross-linking [32].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic analysis was performed using the Universal Analysis 2000 software (version of 4.7A) of TA instruments. Each film sample (10-15 mg) was placed in a desiccator with % RH of 11,22,32,43, 56, 69, 75 and 84 for 72 h and was accurately weighed and then sealed in a DSC aluminum plate; subsequently, each sample was measured, taking an empty aluminum plate as a control. Each sample was first heated up to 100 °C and subsequently quenched to −20 °C.…”
Section: Dsc Testsmentioning
confidence: 99%
“…In quadruplicate, the dried samples were equilibrated in air-tight 1-l Kilner jars containing different saturated salt solutions of known RH at 25 °C. 21 The saturated salt solutions used were lithium chloride, potassium acetate, magnesium chloride, potassium carbonate, sodium bromide, strontium chloride, sodium chloride and potassium chloride, with % RH of 11,22,32,43, 56, 69, 75 and 84, respectively. The samples were weighed periodically (0.0001 g precision) until they attained a constant weight, at which point they were assumed to have reached equilibrium.…”
mentioning
confidence: 99%
See 1 more Smart Citation